Be your own counsellor a step-by-step guide to understanding yourself better - Dainow, Sheila (Piatkus, 1996)
Explores the counselling process in a way which enables people to make the changes they desire to their lives without resorting to an external counsellor. This step-by-step guide aims for greater understanding and acceptance of the whole self - mind, body and spirit.